Analisis Peranan Perkebunan Kopi Robusta Terhadap Perekonomian Kabupaten Kerinci (Dari Aspek Tenaga Kerja) - Febiola Silalahi, Fenny; Wahyuni, Ira; Effran, Endy (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Absorption of labor is one indicator in determining the direction of growth of a region. Regional economic growth will be achieved if it is supported by sectors that contribute to regional economic development. So this study aims to: (1) find out the general description of robusta coffee plantations in Kerinci Regency, (2) analyze the advantages of robusta coffee commodities both statically and dynamically, (3) analyze the growth of robusta coffee plantations in driving the economy in Kerinci Regency seen from the aspects workforce, (4) analyzing the contribution of robusta coffee plantations to the total employment of Kerinci Regency. The data used is secondary data. The data analysis method used was descriptive analysis, location quotient analysis, dynamic location quotient analysis, shift-share analysis and contribution analysis. This research was conducted in Kerinci Regency as the research area and Jambi Province as the reference area. From the results of the study, it can be seen that the development of labor absorption in Robusta coffee plantations shows a fluctuating development every year. Robusta coffee plantations in Kerinci Regency contributed 3.72 Robusta coffee plantations as the base sector. From the results of the DLQ, prospective robusta coffee plantations on employment with an average of 1.93 percent. The results of the shift- share analysis show that at the Jambi Province level, robusta coffee plantations have less potential growth, but at the Kerinci Regency level, the potential for RPs and RPr are 0.27 and -0.26, respectively. The results of the analysis of the contribution of robusta coffee plantations from the aspect of labor absorption are 6.20 percent.